MENGELOLA PERENCANAAN KARIER STAF DALAM SEBUAH ORGANISASI - Mohamad Muspawi (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
Staff career planning is an important thing to be thought of and executed by the leadership. Because without careful planning, staff careers will slowly develop and will slow down to the position he wants, it will certainly harm the staff concerned and also the organization. Career planning has at least two scopes, namely: 1. Planning of rank or rank of employee. 2. Planning the goals of the organization or company. To achieve the planned objectives, it takes seriousness of the staff concerned to work seriously and seriously the leadership in creating and implementing the program and direct the staff to work in accordance with the desired. Preparation of a good career planning needs to pay attention to four main issues, namely: 1. Position of principal and supporting positions. 2. Pattern career path pattern. 3. Structural positions. 4. Grace period.Keywords:  Career planning, staff, organization.